Penggunaan Media Sosial Bagi Petani Muda dalam Berwirausaha di Bidang Pertanian : Use of social media for Young Farmers in Entrepreneurship in Agriculture - Kusuma, Hanarita Naffi; Rozaki, Zuhud; Wulandari, Retno; Suryani, Cahyaningrum Arie (Universitas Muhammadiyah Yogyakarta, 2024)
Social media is a platform where everyone can access it, to share moments and information. Nowadays almost everyone has social media for entertainment or to publish something. over time social media is used as a medium to promote products from a business. This is because social media can reach a wider market at a more affordable cost, social media can also be applied to the agricultural sector, especially to educate the younger generation to be more familiar with agriculture and can pursue agriculture, because currently the majority of farmers in Indonesia are more than 40 years old Where, it is very rare to find young people who are involved in agriculture due to lack of education. Even though we can maximise agricultural yields by utilising technology which is currently very sophisticated, various facilities can be obtained but there are still many who think that farming is very difficult and the benefits are not much, we as the next generation of the nation should care about this, we can contribute to the success of agricultural progress in Indonesia by sharing information about agriculture and inviting the public to realise the importance of the agricultural sector so that social media becomes a very important thing to support the progress of agriculture in Indonesia.